Recycling as a Strategic Direction to Improve Efficiency of Steel Industry in the Russian Federation - V. V. Smirnov (Учёт. Анализ. Аудит, 2018)
The article discusses the issue of increasing the efficiency of the Russian steel industry taking into consideration the requirements of the concept of sustainable development. To solve this problem the author reviews the practices of metal scrap collection and recycling at the leading enterprises of the North America, Europe and the forecast of metal recycling development in the world economy up to the year 2050. This part of the survey shows that technologies of metal scrap and other types of industrial waste recycling could result in considerable economy of different types of resources. The great benefit of using metal scrap recycling technologies by the companies in the United States and the European Union is new jobs creation and improvement of environmental conditions. Taking into account the mentioned benefits of using recycling technologies in steel industry the author analyzes the forecast information and concludes that the further development of steel industry may lead to two times increase in metal scrap collection and recycling by the middle of the XXI century. Companies of the Chinese People Republic, countries members of NAFTA and Japan will prevail in the regional structure of metal scrap consumption. The article also states that the system of metal scrap collection and recycling in the Russian Federation will have to be recreated on the qualitatively new foundation. The most important distinctive feature of a new system still under creation from the former one is that before all the enterprises engaged into metal scrap collection had made part of a single concern and operated as a branch of steel industry. In this regard the Russian Federation faces the problem of re-creation of institutional foundation of metal scrap collection and recycling as well as creation of mechanisms to manage this industry efficiently. This in turn will require the development of legal, regulatory, organizational, economic and scientific support.